![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
23 tháng 5 2016 lúc 8:41
a. /2x-1/=/x+2/
2x-1= x+2 hoặc 2x-1=-x-2
x=3 hoặc 3x=-1
x=3 hoặc x=-1/3
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(21\in B\left(x-3\right)\Leftrightarrow x-3\inƯ\left(21\right)\Leftrightarrow x-3\in\left\{1;3;7;21;-1;-3;-7;-21\right\}\)
\(\Leftrightarrow x\in\left\{4;6;10;24;2;0;-4;-18\right\}\)
Vì \(x\in N\Rightarrow x\in\left\{4;6;10;24;2;0\right\}\)
b, \(1-x\inƯ\left(17\right)\Leftrightarrow1-x\in\left\{1;17;-1;-17\right\}\)
\(\Leftrightarrow x\in\left\{0;-16;2;18\right\}\)
Vì \(x\in N\Rightarrow x\in\left\{0;2;18\right\}\)
c, \(2x+3\in B\left(2x-1\right)\)
\(\Leftrightarrow2x+3⋮2x-1\Leftrightarrow2x-1+4⋮2x-1\Leftrightarrow4⋮2x-1\)
\(\Leftrightarrow2x-1\inƯ\left(4\right)\Leftrightarrow2x-1\in\left\{1;2;4;-1;-2;-4\right\}\)
\(\Leftrightarrow x\in\left\{1;\frac{3}{2};\frac{5}{2};0;\frac{-1}{2};\frac{-3}{2}\right\}\)
Vì \(x\in N\Rightarrow x\in\left\{1;0\right\}\)
d, \(x+1\inƯ\left(x^2+x+3\right)\Leftrightarrow x^2+x+3⋮x+1\Leftrightarrow x\left(x+1\right)+3⋮x+1\Leftrightarrow3⋮x+1\)
\(\Leftrightarrow x+1\inƯ\left(3\right)\Leftrightarrow x+1\in\left\{1;3;-1;-3\right\}\)
\(\Leftrightarrow x\in\left\{0;2;-2;-4\right\}\)
Vì \(x\in N\Rightarrow x\in\left\{0;2\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x.1)(y-3)=7=1*7=7*1=-1*-7=-7*-1
b) x(y+1)+y=1
x(y+1)+y+1=1+1
(y+1)(x+1)=2=-2*-1=-1*-2=2*1=1*2
c)(2x+1)(y-3)=6=2*3=3*2=1*6=6*1=-2*-3=-3*-2=-1*-6=-6*-1
![](https://rs.olm.vn/images/avt/0.png?1311)
2x+12=3(x-7)
2x+12=3x-21
2x-3x=-21-12
x=-33
=> x=33
a,\(2x+12=3.\left(x-7\right)\)
\(=>2x+12=3x-21\)
\(=>2x-3x=-21-12\)
\(=>-x=-33\)
\(=>x=33\)
b,\(2x^2-1=49\)
\(=>x^2=\frac{50}{2}=25\)
\(=>x=\sqrt{25}=5\)
-(2x - 1) + 3 = x + 1
-2x + 1 + 3 = x + 1
4 - 1 = x + 2x
3 = 3x
=> x = 1
\(-\left(2x-1\right)+3=x+1\)
\(-2x+1+3=x+1\)
\(-2x+4=x+1\)
\(-2x+4=x+1\)
\(-2x+4-x=1\)
\(-3x+4=1\)
\(-3x=1-4\)
\(-3x=-3\)
\(x=1\)